Restoration experience through perceived open space qualities and perceived restorativeness of students in Malaysian universities - Malekinezhad, Fahimeh (2018)
Experience of restoration through the application of Perceived Sensory Dimension (PSD) and perceived restorativeness have been shown to reduce stress and improve mental health. Furthermore there are other influential factors on restoration experience such as individual and visit related characteristics as well as need for restoration. However, there is little knowledge on the development of restoration experience model through the impact of PSD and perceived restorativeness that takes into consideration the effects of these influential factors. The research developed a restoration experience model through examining the impact of PSD and perceived restorativeness. In this study, Partial Least Square Structural Equation Model (PLSSEM) was used to examine the interaction among these parameters that developed the restoration experience. Validity and reliability of measurement of restoration experience through the impact of PSD and perceived restorativeness were conducted using 444 students in Malaysian Universities. The results showed that half of the restoration experience was in cases that had higher interactions with campus open spaces, and nearly half of the restoration experience was in cases with lower interaction with campus open spaces. In the former group, experience of restoration was affected by perception of restorativeness through the impact of PSD. On the contrary, in the latter group, restoration experience was more affected through the impact of PSD than perceived restorativeness. Individual related characteristics and need for restoration could not moderate changes in the restoration experience that might have occurred due to the effect of PSD and perceived restorativeness. These findings showed that the experience of restorative outcomes was dependent on the impact of PSD on perceived restorativeness. The effect of visit related characteristics provided information on specific environmental conditions that create experience of higher restorative outcomes. As a conclusion, the research has illustrated that the design of open spaces can promote mental health with a combination of PSD and perceived restorativeness that can be applied in landscape architecture.